VEHICLE TYRE PRESSURE CONTROL AND MONITORING SYSTEMS - Abdulatif Abdubannopov; Yoqutbek Abdumutalov (Journals Park Publishing, 2024)
Based on the analysis of this article, it can be concluded that yres are affected by a large number of factors, understanding that their degree of influence depends on the tyre manufacturer, bus model, climate region, road condition, terrain, etc. It is possible, in the article, that the tyre pressure drops and the wheel spins faster than other wheels due to the reduced radius. Speed differences allow low pressure to be detected and a warning light alerts the driver, but these multi-parameter methods are difficult to implement and require periodic calibration.
Keywords: Car, road, tyre, lines, factors, car, event, wheel, pressure.